2022
DOI: 10.1088/1755-1315/1001/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the liver status of Sentul chickens from the starter phase induced by irradiated chitosan

Abstract: The research aims to examine the effect of irradiated chitosan (ICh) on enzyme levels (SGPT, SGOT, and Gamma Transpeptidase) in the starter phase of Sentul chickens and its physiological conditions, as a result of fungal contamination from the environment (specifically from feed ingredients). This was conducted in the Poultry Production Laboratory, and the sample analysis was performed at the Lab of Animal Physiology and Biochemistry, Padjadjaran University. The samples consisted of 100 Sentul chickens reared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The results of this previous study confirmed that the chemical composition of legumes greatly determines their degradation in the rumen. The results of the same study were also shown by Hernawan et al (2017) and Rahmania et al (2022) that the chemical structure of legumes determines the proportion of protein that can be digested in the rumen to its absorption in the intestine. On the other hand, several types of forage legumes contain anti-nutritional compounds.…”
Section: Introductionmentioning
confidence: 55%
“…The results of this previous study confirmed that the chemical composition of legumes greatly determines their degradation in the rumen. The results of the same study were also shown by Hernawan et al (2017) and Rahmania et al (2022) that the chemical structure of legumes determines the proportion of protein that can be digested in the rumen to its absorption in the intestine. On the other hand, several types of forage legumes contain anti-nutritional compounds.…”
Section: Introductionmentioning
confidence: 55%
“…Regarding cell growth, Gehrke et al (2013); Loyau et al (2014) and Kharazi et al (2022), suggested that lipid synthesis and amino acid metabolism increase sharply during growth, as well as increase the utilization of nutrients Gray et al, 2015;Ippolito et al, 2014;Mushawwir et al, 2020 a,d,e andIstvan et al, 2020;Rahmania et al, 2022). This situation can be supported by the provision of additives such as essential oils.…”
Section: Resultsmentioning
confidence: 98%
“…Other researchers have shown that feeding probiotics to animals and livestock has an impact on their biochemical profiles. These studies demonstrated the ability of probiotics to affect the regulation of protein biosynthesis (hormones and enzymes), as well as specific proteins [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%